Chart of the Antarctic continent shewing the icy barrier attached to it discovered by the U.S. Ex. Ex. Charles Wilkes Esq. Commander - United States North Pacific Exploring Expedition (1853-1856) ([Washington] : United States North Pacific Exploring Expedition, 1840)
No. 70. Includes 5 profile views. Grayscale